Morphology of VIP/nNOS-immunoreactive myenteric neurons in the human gut - Brehmer, Axel; Schrödl, Falk; et al. (Histochemistry and Cell Biology, 2006)
In this study, we characterized human myenteric neurons co-immunoreactive for neuronal nitric oxide synthase (nNOS) and vasoactive intestinal peptide (VIP) by their morphology and their proportion as related to the putative entire myenteric neuronal population. Nine wholemounts (small and large intestinal samples) from nine patients were triple-stained for VIP, neurofilaments (NF) and nNOS. Most neurons immunoreactive for all three markers displayed radially emanating, partly branching dendrites with spiny endings. These neurons were called spiny neurons. The spiny character of their dendrites was more pronounced in the small intestinal specimens and differed markedly from enkephalinergic stubby neurons described earlier. Exclusively in the duodenum, some neurons displayed prominent main dendrites with spiny side branches. Of the axons which could be followed from the ganglion of origin within primary strands of the myenteric plexus beyond the next ganglion (70 out of 140 traced neurons), 94.3% run anally and 5.7% orally. Very few neurons reactive for both VIP and nNOS could not be morphologically classified due to weak or absent NF-immunoreactivity. Another six wholemounts were triple-stained for VIP, nNOS and Hu proteins (HU). The proportion of VIP/nNOS-coreactive neurons in relation to the number of HU-reactive neurons was between 5.8 and 11.5% in the small and between 10.6 and 17.5% in the large intestinal specimens. We conclude that human myenteric spiny neurons co-immunoreactive for VIP and nNOS represent either inhibitory motor or descending interneurons. © Springer-Verlag 2005.
Keywords: Colon; Dogiel classification; Enteric nervous system; Innervation; Neuron type